(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article explores the connection between culture and phraseological units (Phraseological units) that incorporate toponyms, or place names, in both the English and Russian languages. Toponymic Phraseological units are expressions where geographic locations—be they countries, cities, or landmarks—are integral components of the phrase’s meaning. These place-based expressions often carry cultural, historical, and societal significance, as they reflect the cultural attitudes, beliefs, and social norms associated with the places they reference. By comparing English and Russian Phraseological units with toponyms, the article highlights how language and culture are intertwined, demonstrating how geographical knowledge and cultural understanding influence the interpretation and usage of these expressions. The study also includes examples of Phraseological units and provides insights into the challenges and implications for translation and language learning.